Declining numbers of hepatitis C virus-associated liver transplantations in Germany = Rückgang von Hepatitis-C-Virus-assoziierten Lebertransplantationen in Deutschland - Wedemeyer, Heiner; Herzer, Kerstin; Serfert, Yvonne; Taubert, Richard; Trautwein, Christian; Eurich, Dennis; Strassburg, Christian P.; Lang, Melanie; Weiss, Karl Heinz; Berg, Thomas; Galle, Peter R.; Heinzow, Hauke; et al. (Deutsches Ärzteblatt, 2021)
In Germany, the anti-HCV prevalence in the general population is between 0.2 and 1.9% (1). Infection with the hepatitis C virus (HCV) can result in chronic liver disease, the complications of which are liver cirrhosis and hepatocellular carcinoma (HCC). Thus, for many years, HCV infection was one of the most common indications for liver transplantation secondary to decompensated cirrhosis or HCC. Over the past ten years, between 800 and 1200 liver transplantations have been performed in Germany each year. With the introduction of highly effective and safe direct antiviral agents (DAAs) against HCV in 2014, the question arose as to what extent the need for HCV-related liver transplantations has decreased since then. In an initial analysis involving eleven German transplant centers, we already found evidence in 2016 that the proportion of patients with HCV-related liver transplantation was in decline after the introduction of DAA in Germany (2). In this paper we present a follow-up of this study.